(untitled) (American Journal of Technology and Applied Sciences, 2024)
This article explores the fundamental role of financial statements in decoding the language of business and providing stakeholders with a comprehensive understanding of a company’s financial health and performance. By dissecting the key components of financial statements, including the balance sheet, income statement, cash flow statement, and statement of changes in equity, the article highlights their significance for investors, creditors, management, and regulators. Financial statements serve as crucial tools for decision-making, offering insights into profitability, solvency, and overall financial well-being. The analysis emphasizes the universal relevance of financial statements as a means of transparent communication in the dynamic world of finance.